Nurturing comfort: qualitative exploration of pain management techniques among urban teaching hospital nurses - Awube Menlah; Evans Appiah Osei; Gloria Asomani; Isabella Garti; Dorothy Baffour Awuah; Thomas Kwame Asante Tata; Stella Appiah (PAIN Reports)
Abstract. Introduction:. Despite advances in pain assessment and management, pediatric pain remains undertreated, posing a significant challenge including mortalities. This hinders effective pain management for children, often due to difficulties in pediatric pain assessment by nurses. This study explores pain management practices among pediatric nurses at Korle-Bu Teaching Hospital, Accra. Methods:. A qualitative descriptive design was used in this study to select 21 practicing nurses using purposive sampling. A semi-structured interview guide was used to collect data via face-face interviews, and data were analysed using inductive content analysis. Results:. Four major themes and 8 subthemes emerged from the findings. Pediatric pain assessment was primarily guided by the experience of care providers rather than routine practices, with children themselves serving as the main indicators of pain rather than relying on parents. Despite various barriers, health care providers prioritized pediatric pain management by integrating compassion, flexibility, and cultural sensitivity into their approach. Conclusion:. Pediatric nurses were attentive and provided prompt pain relief but faced challenges with pain assessment and medication administration, particularly with suppositories. Implementing standardized protocols for pain management and providing resources to support nurses in overcoming these challenges can improve the quality of care provided to paediatric patients.